2012
DOI: 10.1103/revmodphys.84.1
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium: Stimulating uncertainty: Amplifying the quantum vacuum with superconducting circuits

Abstract: The ability to generate particles from the quantum vacuum is one of the most profound consequences of Heisenberg's uncertainty principle. Although the significance of vacuum fluctuations can be seen throughout physics, the experimental realization of vacuum amplification effects has until now been limited to a few cases. Superconducting circuit devices, driven by the goal to achieve a viable quantum computer, have been used in the experimental demonstration of the dynamical Casimir effect, and may soon be able… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
424
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 469 publications
(435 citation statements)
references
References 186 publications
2
424
0
1
Order By: Relevance
“…It should be stressed that the leftmost cavity, that is, the "single" Fabry-Perot resonator of Figure 4, is initially devoid of any radiation (i.e., it is initially an empty cavity), so that the emission of a macroscopic amount of signal microwaves through the left hole from the left side of the apparatus, would be a dramatic manifestation of the dynamical Casimir effect, in which the observed signal output must have built up exponentially starting solely from vacuum fluctuations inside this initially empty resonator. Since the dynamical Casimir effect is closely related to Hawking radiation according to [32], an observation of parametric oscillation resulting from the moving SC membrane in Figure 4 would be a very interesting result from the point of view of quantum field theory.…”
Section: The Dynamical Casimir Effect Via Parametric Oscillationsmentioning
confidence: 99%
“…It should be stressed that the leftmost cavity, that is, the "single" Fabry-Perot resonator of Figure 4, is initially devoid of any radiation (i.e., it is initially an empty cavity), so that the emission of a macroscopic amount of signal microwaves through the left hole from the left side of the apparatus, would be a dramatic manifestation of the dynamical Casimir effect, in which the observed signal output must have built up exponentially starting solely from vacuum fluctuations inside this initially empty resonator. Since the dynamical Casimir effect is closely related to Hawking radiation according to [32], an observation of parametric oscillation resulting from the moving SC membrane in Figure 4 would be a very interesting result from the point of view of quantum field theory.…”
Section: The Dynamical Casimir Effect Via Parametric Oscillationsmentioning
confidence: 99%
“…This modulates the effective length of the cavity and, as a consequence, its frequency. This modulation acts as an external source of energy leading to parametric amplification [40,41].…”
Section: Degenerate Parametric Amplifier In a Nutshellmentioning
confidence: 99%
“…These properties are utilized for various applications such as the development of the Fluxonion for quantum information precessing 5 , development of voltage standards in metrology 6 and for widely tunable parametric amplifiers 7 . Furthermore it is suggested that very long one-dimensional Josephson junction chains formed in a transmission line geometry can be employed for creating an analog of the event horizon and Hawking radiation 8,9 .…”
Section: Introductionmentioning
confidence: 99%